PEMASARAN DIGITAL UNTUK MENINGKATKAN JUMLAH PENGUNJUNG PADA DESA WISATA PULAU LEMUKUTAN - Dedi Herdiansyah; Meizi Fahrizal; Abdullah Abdullah; Januardi M. Diah; Charlyna S. Purba; Anistya Fitri Larasati; Melti Oktavianda (Politeknik Negeri Sriwijaya, 2022)
Laila Mayaya Park, located in Tanjung Porox, is one of the tourist destinations in Pulau Lemukutan Village, Bengkayang Regency, West Kalimantan Province. Compared to other destinations that have already developed, Laila Mayaya Park can be said to be still minimal in terms of the number of visitors who come, because this location is still included as a new category as a tourist destination. The objectives of this service are as follows: 1). Applying knowledge about digital marketing, 2). Conduct brief counseling and training on digital marketing content creation, and 3). Conducting Focus Group Discussions (FGD) between the two parties, the implementers and the target community. This service is expected to be able to: 1). increase the number of visitors (tourists) so that it will improve financial performance for Laila Mayaya Park, 2). increase knowledge and insight for tourism destination management who can help thinking skills to create attractive digital marketing content for potential visitors, and 3). provide solutions to the constraints of developing tourist destinations for the Laila Mayaya in Tanjung Porox. With the existing knowledge and skills of digital marketing, it is hoped that the main goal of this service is to increase the number of visitors.